Representation of disability in the media: A review of Kenyan newspaper reports of 2015-2016 - Bukhala, Peter W. (Research Journal in Advanced Humanities, 2022)
Throughout history many societies have dealt poorly with disability. In Kenya, persons who have different types of disabling conditions have been excluded or isolated from mainstream society and denied opportunities due to a belief that they may be dangerous and not capable of participating in any meaningful activities. They are denied access to opportunities due to lack of knowledge and cultural beliefs. Even with Kenya having signed and ratified the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) and included these rights in the Constitution in 2010, many cases of injustices continue to pop up in the media. This study was a review of newspaper articles for the year 2015 and 2016 on representation of disability in two Kenyan newspapers - The Standard and the Daily Nation. In the study, existence of negative attitudes, violence, sexual harassment, limited financial support and weak policies were noted. Isolation from society leading to stigmatization was also noted to occur thus making it is hard for people living with a disability to learn daily living skills and integrate in society. Finally, implementation of policies that provide for access to opportunities by those with disabilities at County level of government continues to slow full implementation of policies on disability.